Subcellular localization of the pyoverdine biogenesis machinery of Pseudomonas aeruginosa: A membrane‐associated "siderosome". Issue 21 (13th September 2013) - Imperi, Francesco; Visca, Paolo
Abstract : The peptidic siderophore pyoverdine is the primary iron uptake system of fluorescent pseudomonads, and a virulence factor in the opportunistic pathogen Pseudomonas aeruginosa . Pyoverdine biogenesis is a co‐ordinate process requiring several precursor‐generating enzymes and large nonribosomal peptide synthetases (NRPSs) in the cytoplasm, followed by extracytoplasmic maturation. By using cell fractionation, protein–protein interaction, and in vivo labeling assays we obtained evidence that, in P. aeruginosa, pyoverdine NRPSs assemble with precursor‐generating enzymes into a membrane‐bound multi‐enzymatic complex, for which we propose the name "siderosome". The pyoverdine biogenetic complex represents a novel example of subcellular compartmentalization of a secondary metabolic pathway in prokaryotes. Abstract : Pyoverdine non‐ribosomal peptide synthetases associate with cytoplasmic membrane. l ‐Ornithine‐N 5 ‐oxygenase interacts with pyoverdine nonribosomal peptide synthetases. Pyoverdine biosynthetic enzymes co‐localize on the membrane in P. aeruginosa cells. We denominate the membrane‐associated pyoverdine biosynthetic complex "siderosome".